Pendekatan Pembelajaran Student Teams Achievement Divisions (STAD) Untuk Meningkatkan Hasil Belajar Matematika Peserta Didik Kelas VI MI Al-Khoiriyah Kecamatan Baron Kabupaten Nganjuk - Noor Hafidhoh (Intizam, Jurnal Manajemen Pendidikan Islam, 2020)
The development of the world of education is hampered by various problems, one of which is student learning outcomes. There is an alternative that can be taken to improve student learning outcomes, especially in mathematics. The creativity that teachers have in choosing a teaching model plays a very important role and has a big influence on the learning outcomes of students. Therefore, we need an easy way to convey learning materials. The application of the STAD (Student Teams-Achievement Divisions) type cooperative learning model is expected to motivate students to be more ready to learn mathematics without fear of learning it. Students are expected to train and improve their communication skills and interact with other students in an interesting atmosphere